Shelf life of Manggis Fruit (Garcinia mangostana L.) at Various Fruit Maturity Levels, Temperature, and Types of Packaging - Hasbi .; Daniel Saputra; Juniar . (Jurnal Teknologi dan Industri Pangan, 2005)
The objective of this research was to study the effect of manggis fruit maturity levels, temperature, and types of packaging on the shelf fife of manggis fruit (Garcinia mangostana L), The experimental design used was Factorial Completely Randomized Design with three factors consisting of manggis fruit maturity levels (tinged with purple and brown), packaging types (flexible and stretch film), and storage temperature (l50C and 250C) using two replication for each treatment. The result showed that maturity level had significant effect on weight toss, color but had no significant effect on hardness, total sugar and total acid of manggis fruit during storage. The suitable packaging type to maintain the quality of manggis fruit with maturity level of tinged purple was the flexible type, which result n a shelf life of 33 days. Packaging suitable for manggis fruit with maturity level of brown was the stretch type, which had the shelf life of 39 days. Storage temperature to maintain quality was l50C. Keyword: shelf life. physical quality, chemical quality maturity level, packaging.